Rates of major complications during neoadjuvant and adjuvant chemotherapy for early breast cancer: An off study population. (December 2016) - Redana, S.; Sharp, A.; Lote, H.; Mohammed, K.; Papadimitraki, E.; Capelan, M.; Ring, A.
Abstract: Objectives: To determine the incidence and risk factors for thromboembolic events (TE) and febrile neutropenia (FN) in patients receiving systemic chemotherapy for early breast cancer (EBC). Methods: 325 patients received FEC75, FEC100 -T or ECaP for EBC in 2013. Results: TE occurred in 7.4% and FN in 19.1% of patients. Risk factors for TE were: central venous catheter (p = 0.011). Risk factors for FN were: FEC100 -T treatment versus FEC75 and ECaP (p ≤ 0.001); lower pre-treatment neutrophil count (p = 0.009) and poorer performance status (p = 0.012). Two patients died from treatment-related toxicities. Conclusion: In real-world experience, the majority of patients completed adequate treatment, despite significant complications. Highlights: Chemotherapy major complications are frequently underestimated in off-trial patients with early breast cancer. The incidence of thromboembolic events in this patient population was 7.4% (95% CI 4.8–10.6). The incidence of febrile neutropenia in this patient population was 19.1% (95% CI 15.0–23.4). Thromboembolic events or febrile neutropenia lead to reduced relative dose intensity delivery.